Spontaneous postmenopausal urethral prolapse: A case report and review of literature - (:unkn) unknown (Edizioni Scripta Manent s.n.c., 2012)
Urethral prolapse is a circular protrusion of the distal urethra through the external meatus. It is very rare condition seen mostly in black premenercheal black girl and occasionally in postmenopausal white women. We present a case of spontaneous urethral prolapse in 63-year-old postmenopousal white women with succesful management with estrogen treatment.
Keywords: Menopause; Prolapse; Urethra